2024
DOI: 10.1002/anie.202317776
|View full text |Cite
|
Sign up to set email alerts
|

Binary Atomic Sites Enable a Confined Bidirectional Tandem Electrocatalytic Sulfur Conversion for Low‐Temperature All‐Solid‐State Na−S Batteries

Weiwei Zhang,
Mingli Wang,
Hong Zhang
et al.

Abstract: The broader implementation of current all‐solid‐state Na−S batteries is still plagued by high operation temperature and inefficient sulfur utilization. And the uncontrollable sulfur speciation pathway along with the sluggish polysulfide redox kinetics further compromise the theoretical potentials of Na−S chemistry. Herein, we report a confined bidirectional tandem electrocatalysis effect to tune polysulfide electrochemistry in a novel low‐temperature (80 °C) all‐solid‐state Na−S battery that utilizes Na3Zr2Si2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It can not only be used to synthesize a sulfide solid electrolyte but also serves as a lithium–sulfur cathode. 9–11 When exposed to air, Li 2 S will quickly react with H 2 O to produce the rotten egg-like pungent smell of H 2 S gas, and this will itself also be oxidized by O 2 to deposit sulfur (S). 12 The entire process of synthesizing Li 2 S in the laboratory should be conducted in the glove box where the concentration of H 2 O and O 2 is less than 1 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…It can not only be used to synthesize a sulfide solid electrolyte but also serves as a lithium–sulfur cathode. 9–11 When exposed to air, Li 2 S will quickly react with H 2 O to produce the rotten egg-like pungent smell of H 2 S gas, and this will itself also be oxidized by O 2 to deposit sulfur (S). 12 The entire process of synthesizing Li 2 S in the laboratory should be conducted in the glove box where the concentration of H 2 O and O 2 is less than 1 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…7–10 In this context, the incorporation of inorganic solid electrolytes provides a viable strategy to redress the polysulfide shuttle phenomenon. 11–13 However, the issues of the uncontrollable sulfur speciation pathway remain unresolved. To this end, the development of a quasi-solid state sulfur reversible conversion that dissolves only a small fraction of intermediates provides an ideal platform for tuning the redox chemistry of sulfur species within a solid cell (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,10,12,16,17 However, studies on understanding the sulfur redox in low-temperature (<100 °C) batteries using solid electrolytes are still in their infancy. 13,18–20 Seminal works showed that the soft PEO-NaFSI gel binder could efficiently overcome the interfacial challenges and facilitate a continuous 3D ionic transport path in solid-state metal–sulfur batteries, thus providing a deeper understanding of the redox chemistry during dynamic battery discharge/charge. 21–24 Designing a matrix with a desirable architecture ( e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation